Pemikiran Muhammad Syahrur tentang Wasiat - Elva mahmudi; Elfia Elfia (Jurnal AL-AHKAM, 2019)
Muhammad Syahrur viewed the ulama’s understanding of testaments as being very raw and stagnant so that it did not provide room for movement in resolving later cases. Therefore he suggests new ideas related to the testament which would symbolize that the Koran was indeed “shâlihun lî kulli zamân wa makân”. Syahrur sees the position and application of the testament more than the inheritance. The istinbath method of the Shahrur law is only of two kinds, which are sourced from the Koran and the Sunnah. The difference in views of Shahrur is based on his views on the Koran and the Sunnah which are different from the majority of scholars. In studying the Koran he also relied on sever- al approaches namely: linguistic, philosophical and intra-textual. The thought brought by Syahrur was in contradiction with classical scholars. Therefore, Syahrur’s opinion cannot be freely adopted in responding to the reality of fiqh today and is not one of the forms of renewal of Islamic law. However, what Syahrur did in the testament issue must not all be rejected outright, but there are parts that can be adopted in applying the will law.